MOF-derived carbon nanotube/vertical graphene composite: A binder-free electrode for high-performance supercapacitors with aqueous redox electrolyte - Mingliang He; Jia Qiao; Binghua Zhou; Shien Guo; Guozhen Zhu; Jie Wang; Gan, Melvin Jet Hong; Mingxi Wang; Hironori Ogata; Yoong Ahm Kim; Mauricio Terrones; Morinobu Endo; et al. (Elsevier B.V., 2025)
Vertical graphene (VG), with its unique 3D structure and exceptional properties, is considered an excellent electrode material for supercapacitors. However, the strong hydrophobicity of VG significantly limits its performance in aqueous supercapacitors. In this study, we successfully construct a hybrid carbon nanotubes-vertical graphene-carbon cloth (CNT-VG-CC) structure by converting metal-organic frameworks (MOFs) into carbon nanotubes (CNTs) on the VG surface. This hybrid structure is then employed to fabricate a novel binder-free electrode for hybrid supercapacitors, which operate in a KOH electrolyte with redox additives, K3Fe(CN)6/K4Fe(CN)6. The resulting CNT-VG-CC hybrid structure not only exhibits superhydrophilicity but also offers a large effective specific surface area, enhancing electrolyte contact. The CNT-VG-CC electrode demonstrates an ultrahigh areal capacitance of 1526.5 mF/cm2 at 10 mA/cm2, nearly 100 % coulombic efficiency, and exceptional cycling stability, retaining 100 % of its capacitance after 10,000 charge-discharge cycles. The assembled supercapacitor device delivers a high energy density of 179.7 μW h/cm2 at a power density of 8000.0 μW/cm2. Remarkably, after 10000 cycles, it retains 118.9 % of its initial areal capacitance and maintains a coulombic efficiency of 90.7 %. These impressive performances can be attributed to the unique CNT-VG-CC hybrid structure, its super-hydrophilic property, high electronic conductivity, lager effective specific surface area, and synergistic interaction between the redox electrolyte and the CNT-VG-CC electrode.